The Constructive Power of Slogans in Post-Socialist Poland - Stacul, Jaro (Anthropologica, 2018)
Slogans can tell us a great deal about the ways states attempt to legitimate their neoliberal reform policies, and how the contradictions of the neoliberal project are concealed. Civic Platform, the political force in charge of such reforms that governed Poland from 2007 until 2015, deployed the slogan “We are building Poland” to convey ideas of solidarity and positive change in the face of widespread inequalities. I argue that because slogans have a temporal dimension, understanding their appeal (or lack thereof) entails understanding the ideas about historical time that they mobilise among the people who are exposed to them.